Поліфонічна картина світу в поезії Емілі Дікінсон - Острянко, О. (Літературознавчі обрії. Праці молодих учених, 2010)
The research deals with an analysis of Emily Dickinson’s poetry from the dialogue theory perspective. The communicative space of E. Dickinson’s verse is represented by her religious, puritanic outlook. Besides, this space is clarified by the idea of the absolute equal positions «Me» and «You» in the world of relations. Values and the truth are born in the dialogue. So, author’s ethical position is considered dominant.